Analisis Pengaruh Perubahan Iklim dan Ketersediaan Bahan Baku terhadap Risiko Produksi Batu Bata Merah di Desa Tanah Rakyat Kisaran - Wahyu Yuda Pradana; Sri Ramadhani; Atika Atika (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study examines the effects of climate change and raw material availability on the production risk of red bricks in Tanah Rakyat Village, Kisaran. The researchers used a quantitative method; Data were collected from 55 respondents via questionnaires distributed directly to red brick artisans and analyzed using multiple linear regression with SPSS. The results showed that all instruments were valid and reliable, and that the data were normally distributed. The t-test showed that climate change had a significant effect on production risk (0.002 < 0.05), while the availability of raw materials was not significant (0.114 > 0.05). However, the results of the F-test show that both variables together had a significant effect (0.001 < 0.05). An R² value of 0.229 means that 22.9% of production risk can be explained by the model, with climate change as the dominant factor. This research contributes by providing empirical evidence regarding the dominant impact of climate change on red brick production risks, and by serving as a basis for artisans and local governments to formulate risk mitigation strategies and ensure business sustainability amidst changing environmental conditions.